Effect of Ecbolic Therapy on Postpartum Reproductive Parameters and Serum Hormonal Profile in Dangi Cows - Bhoi, D.B.; Khasatiya, C.T.; Desai , V.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was conducted on eighteen dystocia affected Dangi cows to evaluate the effect of ecbolic therapy on postpartum reproductive parameters as well as serum progesterone and estradiol-17β profile. The cows were randomly divided into three groups, each of 6 animals. The cows in Gr-I and Gr-II were injected with Methyl ergometrine (5 mg) and Dinoprost tromethamine (PGF2α, 25 mg) i/m, respectively, immediately after parturition and the cows of Gr-III received herbal ecbolic boli (2-4 boli, bid, PO) for first 10 days postpartum. The blood samples were collected on 0 day (day of calving), 7th day, 14th day, 21st day and 28th day postpartum from the jugular vein. The mean first postpartum estrus interval in Gr-I, Gr-II and Gr-III were 181.50 ± 44.73 days, 195.33 ± 23.38 days and 155.33 ± 27.81 days. The service period was 237.66 ± 28.01 days with 50 per cent (3/6) conception rate in Gr-I and 402.00 ± 46.12 days and 368.66 ± 53.46 days with 100 per cent (6/6) conception rate in each Gr-II and Gr-III, respectively. The postpartum estrus interval and service period did not differ significantly (p>0.05) between Gr-I, Gr-II and Gr-III. A highly significant (p<0.01) decrease in both progesterone and estradiol-17β concentration was observed on 7th day postpartum and thereafter fluctuated non-significantly with increasing trend on 14th , 21st and 28th day postpartum in all groups.